Growth Performance and Biochemical Composition of Waste-Isolated Microalgae Consortia Grown on Nano-Filtered Pig Slurry and Cheese Whey under Mixotrophic Conditions - Min Su; Marta Dell’Orto; Barbara Scaglia; Giuliana D’Imporzano; Fabrizio Adani (Fermentation, 2022)
The cultivation mode plays a vital role in algal growth and composition. This paper assessed the growth ability of twelve algae–microbial consortia (ACs) originally selected from organic wastes when nano-filtered pig slurry wastewater (NFP) and cheese whey (CW) were used as growth substrates in a mixotrophic mode in comparison with a photoautotrophic mode. Nutrient uptake ability, biochemical composition, fatty acids, and amino acid profiles of ACs were compared between both cultivation conditions. On average, 47% higher growth rates and 35% higher N uptake were found in mixotrophic cultivation along with significant P and TOC removal rates. Changing the cultivation mode did not affect AA and FA composition but improved EAA content, providing the potential for AC_5 and AC_4 to be used as local protein feed supplements. The results also showed the possibility for AC_6 and AC_1 to be used as omega-3 supplements due to their low ω-6–ω-3 ratio.